The Venom of the Boomslang (Dispholidus Typus): In Vivo and in Vitro Studies - Mackay, N; Ferguson, J.C; Bagshawe, Antonia; Forrester, A.T.T; Mcnicol, G.P (Thrombosis and Haemostasis, 1969)
An account is given of the effects of boomslang venom in man. Evidence was found of a fibrinolytic state apparently secondary to the coagulant action of the venom. These features rapidly responded to the administration of specific antivenom. In vitro studies, using a homogenate of boomslang parotids, confirmed the coagulant properties of the venom and showed them to be of much greater potency than the proteolytic actions.